Microbial-induced carbonate precipitation using a sustainable treatment technique / Armstrong Ighodalo Omoregie … [et.al] - Omoregie, Armstrong Ighodalo; Khoshdelnezamiha, Ghazaleh; Leong Ong, Dominic Ek; Nissom, Peter Morin (Universiti Teknologi MARA Cawangan Sarawak, 2017)
Biocementation is a green treatment technique which makes use of microbially induced carbonate precipitation (MICP) process to enhance the geotechnical features of substandard soils. The objective of this study was to conduct a biocement test in laboratoryscale using native urease-producing bacteria to improve the surface strength of poorly graded soil. Selected sand samples were pre-mixed with native bacterial culture and the cementation solution before being compacted into their respective columns. After completing the biocement process, all the sand columns were allowed to air-dry at room temperature (26o C) for 14 days before the treated sands were removed from their respective moulds. Unconfined compression strength (UCS) test was performed on the moulds to determine their strengths, while quick acid test and calcium carbonate (CaCO3) content measurement were conveyed to analyse the precipitated CaCO3 minerals. The results showed that the native urease-producing bacteria could bind soil particles together. The proficiency of this treatment process to improve the strength of soil samples varied among the specimen samples, leading to a non-homogeneous distribution of CaCO3 contents in the specimens. The UCS test showed that the sand treated with native isolate NB 28 had the highest strength (0.219 N/mm2 ), sustaining a force of 1.020 kN, while the control strain (Sporosarcina pasteurii DSM 33) had the lowest strength (0.143 N/mm2 ) with a sustaining force of 0.697 kN. The findings in this study suggest that the native urease-producing bacteria isolated from Sarawak limestone cave can be used as alternative MICP agents for the biocement application for sustainability in the construction industry.